Art in Europe, 1700-1830 - Matthew Craske (Oxford University Press, 1997)
In an era of unprecedented change--rapid urbanization, economic growth, and political revolution--European artists from 1700-1830 were in the business of finding new ways of making, selling, and talking about art. Matthew Craske creates a totally new and vivid record of eighteenth- and early nineteenth-century art in Europe, taking a critical view of such conventional categories as the "rococo," the "neo-classical," and the "romantic." He goes on to explore crucial thematic issues, such as changes in "taste" and manners, and the impact of enlightenment notions of progress, and at the same time goes well beyond the usual geographic limits of surveys to include St. Petersburg, Copenhagen, Warsaw, and Madrid. The result is a refreshingly holistic text which sets the art of the period firmly in its social history